1957
DOI: 10.1128/jb.74.2.234-238.1957
|View full text |Cite
|
Sign up to set email alerts
|

METABOLIC AND SEROLOGIC DIFFERENTIATION OF ACTINOMYCES BOVIS AND “ANAEROBIC DIPHTHEROIDS”

Abstract: It is frequently a difficult task to differentiate Actinomyces bovis from "anaerobic diphtheroids" of questionable pathogenicity. Diphtheroids, isolated from normal and pathological tissues, resemble A. bovis morphologically and in some normal saline, washed, centrifuged, and resus-234

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
1
1

Year Published

1969
1969
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 10 publications
1
9
1
1
Order By: Relevance
“…Puhvel (15) found no acidification of litmus milk, which also conflicts with the results of other authors (5,8,14,16) or our data. Puhvel (15) furthermore stated that the ATCC strains 6921, 6922, and 11827 do not reduce nitrate.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Puhvel (15) found no acidification of litmus milk, which also conflicts with the results of other authors (5,8,14,16) or our data. Puhvel (15) furthermore stated that the ATCC strains 6921, 6922, and 11827 do not reduce nitrate.…”
Section: Discussioncontrasting
confidence: 99%
“…acnes strains, and vice versa, were confirmed both by Voss (19) and by us. Other serological tests (3,8,9,11,15), as well as exhaustive analysis of the fatty acids produced by P. acnes (13,14,16,19), brought only negative evidence. In 1968, Zierdt et al (21) tested their phage 174 on 167 P. acnes strains: 20 of these strains were phage-resistant, and among these at least 9 strains showed still further deviation from the normal spectrum of characteristics.…”
Section: Discussionmentioning
confidence: 98%
“…The characterization of S. epidermidis has been confirmed (16), but that of C. acnes is described very differently in the literature (6)(7)(8)(9)(10)(11)(12). In the 7th edition of Bergey's Manual (15), the anaerobic Corynebacteria were classified into five species: C. acnes, C. parvum, C. granulosum, C. avidum and C. diphtheroides.…”
Section: ) the Quantitative Analysis Of Propionic Acid In Incubated mentioning
confidence: 98%
“…Furthermore, several studies have demonstrated that C. acnes is lipolytic (2,3) and this is thought to be the most important pathogenic factor in acne vulgaris, an inflammatory process involving the pilosebaceous units of human skin (4,5). The characters of C. acnes are described very differently III the literature (6)(7)(8)(9)(10)(11)(12). Certain characters of C. acnes are particularly controversial.…”
mentioning
confidence: 99%
“…Andere Untersucher stiefien sicher schon um die Jahrhundertwende auf aerobe Nocardia-Arten als Erreger aktinomykoseahnlicher Krankheitsprozesw, die heute unter dem Namen Nocardiosen zusammengefafit werden. Die pathologische Verwandtschafl der Rinder-Aktinomykose mit der humanen, die Ahnlichkeit der Drusenbildung und Kulturvergleiche stutzten lange Jahre die Auffassung von der Identitat der Erreger beider Erkrankungen (19,26,37,38,70,98,116,120,133). LENTZE (75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85) bewies schlieRlich mit einem umfangreichen Material die atiologische Bedeutung des Actinomyces israeli fur die humane Aktinomykose.…”
unclassified